1998
DOI: 10.1007/bf02468493
|View full text |Cite
|
Sign up to set email alerts
|

Cold treatment of steel

Abstract: A. P Gulyaev belongs to the category of scientists who possess a universal knowledge in the field of metal science. In fact his thought worked in virtually any direction the science developed. He has equally mastered the problems of diffusion in solid bodies, alloying, strength and fracture, toughness and brittleness, plasticity and superplasticity, deformation, and heat and chemical heat treatment. He had a rare girl of foreseeing the results, determining the essence of the problems, and making an optimum exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Many authors have referred to the benefits of controlled immersion in a cooling media [2][3][4]. Other mediums-brine, alcohol/water mixtures-were used before the advent of cryogenic processors, or cryoboxes, to enable controlled cooling and soaking in liquid nitrogen (LN).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have referred to the benefits of controlled immersion in a cooling media [2][3][4]. Other mediums-brine, alcohol/water mixtures-were used before the advent of cryogenic processors, or cryoboxes, to enable controlled cooling and soaking in liquid nitrogen (LN).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the fraction of RA, Mathews proposed to further reduce the temperature after conventional hardening by cooling below zero Celsius, for example by immersion of the parts in liquid air, i. e. to -183 °C. In the two following decades, Mathews' hypothesis was confirmed by various authors, of which Gulyaev [8] and Cohen and his co-workers [9,10] are probably best known. In particular, Cohen et al showed that the austenite-to-martensite transformation continues in steel on cooling to -150 °C; further cooling would be ineffective.…”
Section: The Concept Of Cryogenic Treatment and The Initial Refusalmentioning
confidence: 92%
“…B. durch Eintauchen der Teile in flüssige Luft, d. h. auf -183 °C. In den beiden folgenden Jahrzehnten wurde Mathews Hypothese von verschiedenen Autoren bestätigt, von denen Gulyaev [8] und Cohen und seine Mitarbeitenden [9,10] wohl am bekanntesten sind. Cohen et al zeigten insbesondere, dass sich die Austenit-Martensit-Umwandlung im Stahl bei einer Abkühlung auf -150 °C fortsetzt; eine weitere Abkühlung wäre wirkungslos.…”
Section: The Concept Of Cryogenic Treatment and The Initial Refusalunclassified
“…Because DCT is known to accelerate the decomposition of martensite and precipitation of SCs during tempering, the selection of lower temperature and/or shorter duration of soaking is recommended for the tempering of cryogenically hardened tool steels. 2 Furthermore, in order to avoid loss of hardness due to over tempering, cryogenically hardened samples should be subjected to single tempering only, 33,45,46 in place of double or triple tempering cycles commonly employed for the conventionally hardened tool steels. 32 These modifications of tempering treatment not only reduces the total processing time but also partly balances the cost incurred due to the incorporation of CP cycle in cryotreatment.…”
Section: Process Of Cryogenic Treatmentmentioning
confidence: 99%